PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Siska Evelina Br Depari; Saut Mahulae; Regina Sipayung; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the effect of the STAD-typed cooperative learning model on students' mathematics learning outcomes in class V of SDN 040529 Ajibuhara Tiga Panah Karo in the academic year of 2020/2021. The research approach used in this article was quantitative. The sampling technique used was saturated sampling and involved a number of 31 students. The results indicated that students’ learning outcomes using the STAD model were categorized as very good with an average score of 80.64. It was achieved the normality testing with a significance value of 0.20, thus, 0.20 > 0.05 from the data of class V was normally distributed. In the correlation testing, the correlation coefficient was 0.371 with a significance of 0.040, which means rcount (0.371) > rtable (0.355). Hence, there was a positive correlation between the STAD model and students' mathematics learning outcomes, which was 2.150 > 1.826. Thus, Ha is accepted. It shows that there was a positive and significant effect of the STAD learning model on student learning outcomes.